FILSAFAT POSITIVISTIK SOSIAL AUGUSTE COMTE - Ekawati, Melinda Nur; Usman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This article discusses the philosophical thought of social positivism developed by Auguste Comte as a response to the dominance of church dogma during the Middle Ages. The aim of this study is to explore the epistemology of social positivism as a foundation for building a scientific basis for the social sciences. This research employs a qualitative approach using a literature review method. Data for this study were obtained from various relevant literary sources. The findings indicate that Auguste Comte classified the development of human knowledge into three stages: theological, metaphysical, and positive. Comte emphasized that scientific knowledge must be based on empirical facts that are observable and systematically measurable, including in the study of social phenomena. Sociology, as the highest science in Comte’s classification, is responsible for coordinating the development of other sciences by employing methods such as observation, comparison, and historical analysis. Comte’s thought made a significant contribution to the development of scientific paradigms in the social sciences by rejecting metaphysical approaches and prioritizing a scientific-positivistic approach.